A secretory multifunctional serine protease, DegP of Plasmodium falciparum, plays an important role in thermo‐oxidative stress, parasite growth and development. (24th February 2014) - Sharma, Shweta; Jadli, Mohit; Singh, Anu; Arora, Kavita; Malhotra, Pawan
<x xml:space="preserve">Abstract</x> Plasmodium falciparum heat shock proteins and proteases are known for their indispensable roles in parasite virulence and survival in the host cell. They neutralize various host‐derived stress responses that are deleterious for parasite growth and invasion. We report identification and functional characterization of the first DegP from an apicomplexan (P. falciparum). To determine the molecular identity and functions of the parasite‐encoded DegP, we complemented the Escherichia coli degP null mutant with a putative PfdegP gene, and the results showed that PfDegP complements the growth defect of the temperature sensitive DegP‐deficient mutant and imparts resistance to non‐permissive temperatures and oxidative stress. Molecular interaction studies showed that PfDegP exists as a complex with parasite‐encoded heat shock protein 70, iron superoxide dismutase and enolase. DegP expression is significantly induced in parasite culture upon heat shock/oxidative stress. Our data suggest that the PfDegP protein may play a role in the growth and development of P. falciparum through its ability to confer protection against thermal/oxidative stress. Antibody against DegP showed anti‐plasmodial activity against blood‐stage parasites in vitro, suggesting that PfDegP and its associated complex may be a potential focus for new anti‐malarial therapies. Structured digital abstract ●PfDegPphysically interacts with PfHsp70 and PfEno by anti-bait co-immunoprecipitation (View interaction) ●PfDegPphysically interacts with PfEno, PfSod, PfOat, PfHsp70, PfLDH and PfGpi by anti-bait co-immunoprecipitation (View interaction) ●PfHsp-70 and PfDegPco-localize by fluorescence microscopy (View interaction) ●PfDegPphysically interacts with PfOat, PfHsp70, PfEno, PfSod, PfGpi and PfLDH by surface plasmon resonance (View interaction) ●PfEno and PfDegPco-localize by fluorescence microscopy (View interaction) ●PfDegP and PfHsp70co-localize by co-sedimentation through density gradient (View interaction)